Extrusion process of 7075 aluminum alloy bicycle seat post using finite element analysis - Dyi-Cheng, Chen; Ming-Wei, Guo; Fung-Ling, Nian (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.